(untitled) (Germany, 2006)
Substitution of hazardous substances is a prioritised objective in chemical regulation and risk management. However, it is experienced as a tough task with often inconsistent results. Based on thirteen case studies, this book analyzes substitution as an innovation process and attempts to give answers to the following questions: Why and under which circumstances are companies able and willing to substitute hazardous substances? What are the main drivers and the main barriers? In which way can communication along the supply chain support environmental innovation? How can risk management appropriately deal with the lack of knowledge, with uncertainties and incomplete knowledge about the possible effects of different substances? Recommendations for action are provided for commercial and state institutions and consumers and thus for all actors engaged in the European reform of chemicals policy following the REACH system.
Keywords: Hazardous substances,Chất nguy hiểm độc hại,Environmental exposure,Hazardous substances,Phơi nhiễm môi trường,Chất nguy hiểm độc hại; Prevention & control,Environmental aspects,Kiểm soát và ngăn ngừa,Khía cạnh môi trường